Effects of heat treatment and homogenization on milk fat globules and proteins in whipping creams. (April 2017) - Matsumiya, Kentaro; Horiguchi, Sanae; Kosugi, Tatsuya; Mutoh, Taka-Aki; Nambu, Yuko; Nishimura, Kimio; Matsumura, Yasuki
Graphical abstract: Highlights: The quality of whipping creams varies with processing. Stability against solidification and whippability should be controlled. Colloidal properties of fat globules of the creams were studied. The amount of proteins on fat globules should play an important role. Second homogenization exerted a strong impact on the protein amount. Abstract: The stability against solidification during storage and whippability of commercial cream products vary depending on the repetition of heat treatment and homogenization necessary for extended shelf-life. First, the two commercial creams subjected to different times of heat treatment and homogenization were investigated. Among several factors such as the colloidal properties, melting profiles of fat globules and protein content and composition, the amount of proteins present at the fat globule surfaces should play a major role in determining the cream quality probably in relation to the degree of expected partial coalescence of fat globules during transportation and whipping, while the composition of proteins adsorbed to the oil–water interface was not the critical factor affecting the quality of creams. A further step-wise preparation of cream samples in a laboratory scale revealed that the second homogenization significantly reduced the amount of proteins adsorbed to the surface of fat globules. There is a possibility that physical and colloidal macro-ordered properties of whipping creams can be controlled by appropriately managing the homogenization process.